Pensions and Fertility: Back to the Roots - The Introduction of Bismarck's Pension Scheme and the European Fertility Decline - Robert Fenge; Beatrice Scheubel (Center for Economic Studies and ifo Institute (CESifo), 2013)
Fertility has long been declining in industrialised countries and the existence of public pension systems is considered as one of the causes. This paper is the first to provide detailed evidence based on historical data on the mechanism by which a public pension system depresses fertility. Our theoretical framework highlights that the effect of a public pension system on fertility works via the impact of contributions in such a system on disposable income as well as via the impact on future disposable income that is related to the internal rate of return of the pension system. Drawing on a unique historical data set which allows us to measure these variables a jurisdictional level for a time when comprehensive social security was introduced, we estimate the effects predicted by the model. We find that beyond a general depressing effect of social security on birth, a lower internal rate of return of the pension system is associated with a higher birth rate and a higher contribution rate is associated with a lower birth rate.
Keywords: C21; H31; H53; H55; J13; J18; J26; N33; 330; public pension; fertility; transition theory; historical data; social security hypothesis